2014
DOI: 10.1108/mmms-12-2013-0078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of static axial compression on the natural frequencies of helical springs

Abstract: Purpose -The purpose of this paper is to address the practically important problem of the load dependence of transverse vibrations for helical springs. At the beginning, the author develops the equations for transverse vibrations of the axially loaded helical springs. The method is based on the concept of an equivalent column. Second, the author reveals the effect of axial load on the fundamental frequency of transverse vibrations and derive the explicit formulas for this frequency. The fundamental natural fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
1
10
0
1
Order By: Relevance
“…He derived the explicit formulas for the fundamental natural frequency of the transverse vibrations of the spring depends on the variable length of the spring. The reduction of frequency with the load was demonstrated by Kobelev (2014). In this study, similar to the Reference (Yıldırım, 2009a), it was shown that when the frequency nullifies the spring buckling occurs.…”
Section: Introductionsupporting
confidence: 84%
See 3 more Smart Citations
“…He derived the explicit formulas for the fundamental natural frequency of the transverse vibrations of the spring depends on the variable length of the spring. The reduction of frequency with the load was demonstrated by Kobelev (2014). In this study, similar to the Reference (Yıldırım, 2009a), it was shown that when the frequency nullifies the spring buckling occurs.…”
Section: Introductionsupporting
confidence: 84%
“…As it is well known, the critical buckling loads may also be determined in a dynamic manner (Yıldırım, 2012;Kobelev, 2014). In this method, for a given static axial load, from 0 P to cr P at which the fundamental frequency of the spring becomes zero, the fundamental frequencies of the spring are searched.…”
Section: Numerical Example For Buckling and Free Vibration With A Stamentioning
confidence: 99%
See 2 more Smart Citations
“…[33]. The Haringx model was also used in study [34] to determine the natural frequencies of transverse vibrations of a simply supported spring. It was pointed out, in [35], that the above-mentioned equivalent rod concept, proposed in [22] for the analysis of elastic stability of helical springs, can also be applied in the analysis of natural transverse vibrations of helical springs.…”
Section: Introductionmentioning
confidence: 99%